2022
DOI: 10.1038/s41598-022-19696-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of late-life body mass index with the risk of Alzheimer disease: a 10-year nationwide population-based cohort study

Abstract: Existing data for the association between late-life body mass index (BMI) and the risk of Alzheimer’s disease (AD) in the underweight population are limited with conflicting results. A large population-based cohort study of 148,534 individuals aged ≥ 65 years who participated in the national health screening program from 2002 to 2005 was performed using the Korean National Health Insurance Service-Senior cohort database 2006–2015. The risk of AD according to BMI category (kg/m2) in Asians was evaluated using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For individuals with high late-life BMI, AD's HR came out as 0.902. (95% CI 0.79-1.02), while those with greater midlife to late-life BMI reduction had a 20% higher chance of AD (95% CI 0.99-1.42) (Cho et al 2022). Older individuals had a lower Aβ burden and more enormous hippocampal volume.…”
Section: The Obesity Epidemicmentioning
confidence: 96%
See 1 more Smart Citation
“…For individuals with high late-life BMI, AD's HR came out as 0.902. (95% CI 0.79-1.02), while those with greater midlife to late-life BMI reduction had a 20% higher chance of AD (95% CI 0.99-1.42) (Cho et al 2022). Older individuals had a lower Aβ burden and more enormous hippocampal volume.…”
Section: The Obesity Epidemicmentioning
confidence: 96%
“…This research intended to explore AD demographics, including prevention methods, risk factors and public health insights (Franks et al 2021). Figure 1 shows the overall review of factors affecting AD demographics: preventive strategies, risk assessments and public health perspectives in this study (Cho et al 2022).…”
mentioning
confidence: 99%
“…Another study showed similar patterns of brain atrophy and AD pathology in obesity compared to AD patients matched by age and sex [ 6 ]. Interestingly, although obesity in midlife is associated with lower brain volumes and a higher risk of AD, obesity in late life (after age 70 years) is associated with decreased AD risk [ 2 , 7 ] and higher BMI is negatively associated with cortical β-amyloid content in older adults [ 8 - 10 ]. In addition, higher body fat content, lower muscle mass, and higher fat-to-muscle ratio were associated with better cognitive performance and lower risk of all-cause dementia in elderly participants, especially in males [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%